Interconector urbano de infraestructura intermodal (2017)
"The implementation of the metro system in Bogotá represents the opportunity to set a turning point in the development of transportation in the city. In other words, replacing private traffic throughout the metro line by bicycle paths and a tram system contributes to the reduction of motorized vehicles usage, expands pedestrian life, and facilitates a more sustainable understanding of this infrastructure. The node of Los Heroes is a potential starting point for the first line of the metro and for the densification that decree 621 of 2017 permits. An area of interconnection of urban systems is proposed to contribute to the sustainable development of infrastructures and quality of life of the citizens. This project promotes the sustainable development of public transportation in Bogotá." -- Tomado del Formato de Documento de Grado.